MANAGEMENT OF INVASIVE ALIEN WEED (PARTHENIUM HYSTEROPHORUS L) THROUGH ALLELOPATHIC AND COMPETITIVE PLANTS AND CHEMICALS IN ETHIOPIAN AGRICULTURE - Zehara Mohammed Damtew (Engineering Heritage Journal)
The study conducted evaluated potential of extracts of selected plant species and chemicals on growth of P. hysterophorus. Since the impact of parthenium weed has become to the status of being an extensive economic and social problems of Ethiopian farmers. The experiment identified herbicidal potential of Aregemon mexicana leaf, stem and root extracts and 2, 4-D on seed germination and early seedling growths of parthenium at under field pot condition. Aqueous extracts of 6, 8 and 10 % (w/v), obtained from dry leaves, stem root of Aregemon mexicana plants and 0.3, 0.5 and 0.7 % of 2, 4-D herbicide. The overall germination, shoot and root growth means of A. mexicana extract and 2, 4-D, herbicidal treatments were significant (p<0.0001). Germination hinder by 2, 4-D and A. mexicana stem extracts, which inhibited the germination by (74.4 and 69.3 %) respectively from the control (82.2 %) and the lowest was A. mexicana root extract (54.8 %) in invitro. In the pot experiment the overall growth parameter means of plant extract and herbicidal treatments were significantly lower than the distilled water treated plants. A. mexicana stem resulted 100 % mortality at active growth stage of the parthenium plant, and 2, 4- D also showed best suppressed growth effects. A. mexicana leaf and root gave remarkable seed suppression of (93-94%) at 10 % concentration. Then we conclude that species like A. Mexicana and chemicals like 2, 4-D and are good candidates for future parthenium management. The Small holder farmers adopted mechanical control measures, while, it is most serious is not tackled by these farmers, integrate with other management options such as competitive plants and chemicals may appear to be satisfactory. However further research is required to progress our understanding of the interference mechanisms between parthenium and these species, on how to integrate with other management options and cost effectiveness of the methods.